Student Perceptions on Problem-Based Learning (PBL) in Learning to Speak English of Tenth-Grade at SMA Swasta Masehi GBKP Berastagi - Sihotang, Rosanti Br; Dewi, Ni Luh Putu Eka Sulistia; Juniarta, Putu Adi Krisna (English Education Department STKIP Agama Hindu Singaraja, 2023)
This study focuses on describing the perceptions of tenth grade students in learning Problem Based Learning in English-speaking classes at SMS Swasta Masehi GBKP Berastagi. This study was a mixed method study. Data collection in this study was carried out through questionnaires and interviews. The results of data analysis confirm that: (1) All students of class ten IPA-1 SMA Swasta Masehi GBKP Berastagi have a fairly satisfied perception of problem-based learning method in learning English in the oral class. (2) Problem based learning increase students’ confidence to speak English either by presenting or discussing with friends. (3) Some introvert students have a little problem in the problem-based method but can be tricked by the teacher occasionally giving problems to be solved privately. (4) English teachers who teach in class ten IPA-1 SMA Swasta Masehi GBKP Berastagi feel an increase in students' desire to learn English at every meeting. Problem-based learning is encouraged in enhancing students speaking skill.